Association of Serum Magnesium Levels with Matrix metalloproteinase-9 (MMP-9) Urine in Patients with Diabetic Kidney Disease Stage 1 and 2 - Rafsanjani, M. Hashemi; Wibisono, Sony; Irwanadi, Chandra (Biomolecular and Health Science Journal, 2019)
Introduction: The progressiveness of stage 1 and 2 kidney disease is indicated by an increase in matrix metalloproteinase-9 (MMP-9). Development of diabetic kidney disease (DKD) is characterized by a thuckening of the glomerular basement membrane followed ultimately by progression to glomerular sclerosis and fibrosis. One of the factors that contribute is magnesium levels. This study aimed to determine the association between serum magnesium levels and MMP-9 urine in patients with stage 1 and 2 DKD.Methods: This was a cross sectional study from stage 1 and 2 DKD patients. Patients were examined for serum magnesium levels and urine MMP-9. Urine MMP-9 examination was taken from the middle portion urine collection and examined using Sandwich-ELISA method then normalized with urine creatinine. The correlation between magnesium and MMP-9 urine was analyzed by the Spearman rank test.Results: This study involved 56 subjects. The mean serum magnesium level was 1.8 ± 0.26 mg/dL. The mean MMP-9 was 120 ng/g creatinin. The mean value of FBG (fasting blood glucose) in patients in the study was 153.29±50.22 mg/dL. The mean value of PPG (post prandial glucose) was 233.61±71.3 mg/dL. The mean HbA1c value was 7.6±1.13%. The mean creatinin serum value was 1.1±0.43 mg/dL. There was a significant negative relationship with a moderate correlation between serum magnesium levels and urine MMP-9 (p = 0.000, r -0.512).Conclusion: There was a significant negative relationship between serum magnesium levels and urine MMP-9 in stage 1 and 2 DKD patients.